DAMPAK KEBERADAAN PERGURUAN TINGGI TERHADAP TINGKAT KESEJAHTERAAN PELAKU USAHA KANTIN (Studi kasus di Dusun Senyawan Desa Sebayan, Kecamatan Sambas, Kabupaten Sambas) - Al Amin; Sumar’in, Ahmad Yasir (CV. Adiba Aisha Amira, 2025)
The existence of a university in an area not only has an impact on the educational aspect, but also brings significant changes to the social and economic conditions of the surrounding community. This phenomenon is clearly seen in Senyawan Hamlet, Sebayan Village, Sambas District, which experienced an economic transformation after the establishment of the Sultan Muhammad Syafiudin Sambas Islamic Institute and the Sambas State Polytechnic. Before the existence of a university, the majority of the Senyawan Hamlet community worked as farmers with limited income. However, along with the increasing number of students, various business opportunities emerged, one of which was the canteen business which was growing rapidly around the campus. This study aims to analyze the impact of the existence of a university on the welfare level of canteen business actors in Senyawan Hamlet. In addition, this study also seeks to identify the obstacles faced by business actors in improving their welfare. The research method used is a qualitative approach with data collection techniques through observation, in-depth interviews with canteen business actors, and documentation. The results of the study show that the existence of a university has a significant economic impact on the local community. Canteen business actors experienced an increase in income compared to their previous professions, such as farmers and migrant workers. The canteen business is a rapidly growing sector because it has a fast capital turnover and stable demand from students. However, despite providing economic benefits, canteen business actors face several challenges, such as tight competition, fluctuations in raw material prices, and dependence on the number of students who decrease during academic holidays.